Sport, sex and age increase risk of illness at the Rio 2016 Summer Paralympic Games: a prospective cohort study of 51 198 athlete days - Derman, W.; Schwellnus, M. P.; Jordaan, E.; Runciman, P.; Blauwet, C.; Webborn, N.; Lexell, J.; Van de Vliet, P.; Tuakli-Wosornu, Y.; Kissick, J.; Stomphorst, J. (British Journal of Sports Medicine, 2018)
Abstract: Objective To describe the epidemiology of illness at the Rio 2016 Summer Paralympic Games. Methods: A total of 3657 athletes from 78 countries, representing 83.5% of all athletes at the Games, were monitored on the web-based injury and illness surveillance system (WEB-IISS) over 51 198 athlete days during the Rio 2016 Summer Paralympic Games. Illness data were obtained daily from teams with their own medical support through the WEB-IISS electronic data capturing systems. Results: The total number of illnesses was 511, with an illness incidence rate (IR) of 10.0 per 1000 athlete days (12.4%). The highest IRs were reported for wheelchair fencing (14.9), para swimming (12.6) and wheelchair basketball (12.5) (p<0.05). Female athletes and older athletes (35-75 years) were also at higher risk of illness (both p<0.01). Illnesses in the respiratory, skin and subcutaneous and digestive systems were the most common (IRs of 3.3, 1.8 and 1.3, respectively). Conclusion: (1) The rate of illness was lower than that reported for the London 2012 Summer Paralympic Games; (2) the sports with the highest risk were wheelchair fencing, para swimming and wheelchair basketball; (3) female and older athletes (35-75 years) were at increased risk of illness; and (4) the respiratory system, skin and subcutaneous system and digestive system were most affected by illness. These results allow for comparison at future Games